The Effect of Facility and Quality of Service on Passenger Satisfaction at Terminal 3 Airport Soekarno Hatta on The Covid-19 Pandemic - Intan, Chyntia Sri; Lois, Lingga; Wahyuni, Rr. Endang; Kholdun, Amrulloh Ibnu (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
The purpose of this study was to determine the effect on facilities and service quality on passenger satisfaction during the Covid-19 pandemic. The population of thus research is passengers at Terminal 3 Soekarno Hatta International Airport. The method used in this research is quantitative method with data analysis technique using validity test, reliability test, multiple linear regression test, multiple correlation coefficient test, multiple determination coefficient test, Classical Assumptions, namely multicollinearity test, T test and F test. The result of data processing in this study, facilities and service quality have a positive and significant effect partially or simultaneously, It means that passengers are satisfied with the facilities and service quality at Terminal 3 Soekarno Hatta International Airport.